Monopsony in Labor Markets: A Review. (January 2021) - Manning, Alan
Researchers' interest in monopsony has increased in recent years. This article reviews the accumulating evidence that employers have considerable monopsony power. It summarizes the application of this idea to explaining the impact of minimum wages and immigration, in anti-trust, and in understanding how to model the determinants of earnings in matched employer–employee data sets and the implications for inequality and the labor share.